Pests Associated with Mulch and Moisture - P.G. Koehler; J.L. Castner (EDIS, 1997)
This document provides an overview of pests associated with mulch and moisture, including booklice, plaster beetles, centipedes, amphipods, earwigs, millipedes, pillbugs, sowbugs, fungus gnats, and springtails. It describes their physical characteristics, habitats, and behaviors, emphasizing the conditions that lead to infestations. The publication highlights the importance of understanding these pests for effective management and control. Original publication date January 1994.